In vitro approaches to the identification and characterization of skin sensitizers. (August 2013) - Vocanson, Marc; Nicolas, Jean-Francois; Basketter, David
Abstract : Allergic contact dermatitis is a disease that to a great extent can be limited or even avoided. Limitation of allergic contact dermatitis can be realized by the predictive identification of sensitizing chemicals (hazard identification), measurement of their relative sensitizing potency (hazard characterization) and subsequent use of proper risk assessment/management strategies in relation to the anticipated skin exposure. Several in vivo methods exist that are known to be reliable predictors of chemicals that can behave as skin sensitizers. One particular method, the local lymph node assay, also produces vital information on the relative potency of identified sensitizers. This potency information can be applied to quantitative risk assessment for skin sensitization, although the completion of quantitative risk assessment is dependent also on access to information on human skin exposure. However, the challenge in 2013 is how to obtain the same type of information on the potency of skin sensitising chemicals using only in vitro and in silico methods. With the impending elimination of in vivo tests, the in vitro test development focus has been on the essential mechanistic steps of sensitization induction, including hapten–peptide binding, dendritic cell migration/maturation and T-lymphocyte priming. Several in vitro methods appear close to successful validation for hazard identification. What has to be addressed is how information from such in vitro assays is integrated, together with data on epidermal bioavailability, to deliver hazard characterization in the form of assessment of sensitizer potency. More than a single protocol, a battery of different in vitro tests will be probably necessary to optimize the detection of skin sensitizers.